Ð˜ÑÐ¿Ð¾Ð»ÑŒÐ·Ð¾Ð²Ð°Ð½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð¹ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ð°Ñ€Ð½Ð¾Ð¹ Ñ‚ÐºÐ°Ð½Ð¸ Ð² Ð»ÐµÑ‡ÐµÐ½Ð¸Ð¸ Ð½ÐµÐ²Ñ‹Ð½Ð°ÑˆÐ¸Ð²Ð°Ð½Ð¸Ñ Ð±ÐµÑ€ÐµÐ¼ÐµÐ½Ð½Ð¾ÑÑ‚Ð¸ - Grischenko, V. I.; Lazurenko, V. V.; Prokopyuk, O. S.; Aralov, O. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2003)
The results of cryopreserved placental tissue (CPT) application for keeping pregnancy and when treating its failure resulted from immunological and hormonal shifts in blood of pregnant woman.